Learning for economic self sufficiency : constructing pedagogies of hope among low-income, low-literate adults - Alfred, Mary V., 1951- (Adult education special topics., 2010)
In a most timely volume addressing many of the connections among current fiscal and employment crises to adult education, Learning for Economic Self-Sufficiency highlights the problems and challenges that low-literate adults encounter in various environments. Moreover, this book presents strategies for addressing the chronic illiteracy among low-income workers. The power of this volume is that the reader gains a holistic view of the complexities of educating a population of low-literate adult learners from various life conditions. From language literacy issues in corrections, the workplace and access to higher education, and migrant workers literacy learning barriers, to technology literacies, and consumerism myths, Learning for Economic Self-Sufficiency goes far deeper than prior volumes in exploring the complex scope of issues face by low-income, low-literate adults as they seek learning for economic self-sufficiency.The overall objective of the book is to help readers explore economic self-sufficiency for low literate and low-income adults from various contexts and the role of adult and higher education in developing these learners for greater economic independence. Noting that literacy is only a first step to economic, mental, and physical health as well as responsible citizenship, each chapter provide specific case examples and recommendations to educators and trainers of adults for creating learning programs and environments to facilitate the development of a more literate and economically stable population.